Positive electrode material precursor and preparation method thereof, positive electrode material, battery and power-related equipment
By optimizing the morphological design of the precursor of the positive electrode material, secondary particles with porous structures are formed, which solves the problems of slow transfer of lithium ions and high-temperature sintering in lithium batteries, improves capacity, magnification and cycling performance, and improves the overall performance of the battery.
Patent Information
- Application Number
- CN202411441065.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
AI Technical Summary
The morphology and structure of traditional positive electrode materials lead to slow migration of lithium ions, limiting the capacity and rate performance of lithium batteries. At the same time, high-temperature sintering can easily destroy the crystal structure and reduce circulation and safety performance.
Using the hydroxide positive electrode material precursor containing transition metal, the morphological design is optimized to form secondary particles with porous structures, with a particle size of 6 to 25 μm, an average cross-sectional porosity of 25 to 55%, and a core layer and a shell layer. Layered structure reduces the interface resistance of lithium ion migration, reduces sintering temperature, and improves electron conduction rate and battery performance.
It significantly improves the capacity, rate performance and cycling performance of lithium batteries, maintains the crystal structure consistency of the positive electrode material, and improves the safety performance of the battery.
Smart Images

Figure CN119284986A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a positive electrode material precursor and a preparation method thereof, a positive electrode material, a battery and electrical equipment. Background Art
[0002] The positive electrode material precursor is the front-end material of the positive electrode material in the lithium battery and plays a decisive role in the performance of the positive electrode material.
[0003] Traditional positive electrode materials are restricted by the inherent morphology and structural composition of the positive electrode material precursor. During the charge and discharge process of the positive electrode material, lithium ions need to pass through more interfaces to migrate, which makes the lithium ion transmission kinetics relatively slow, making it difficult to further increase the battery capacity; at the same time, lithium ions are difficult to migrate quickly under high current conditions, which severely limits the battery's rate performance. In addition, during the process of sintering the positive electrode material precursor into the positive electrode material, the crystal structure is easily destroyed under high-temperature sintering, resulting in poor consistency of the positive electrode material crystal structure and poor battery cycle performance and safety performance.
[0004] In view of the above, the present invention is proposed. Summary of the invention
[0005] The present application provides a positive electrode material precursor and a preparation method thereof, a positive electrode material and a lithium battery, aiming to solve the above-mentioned problems or at least alleviate the defects existing in the above-mentioned prior art.
[0006] The first aspect of the present application provides a positive electrode material precursor, which is a transition metal-containing hydroxide, and the positive electrode material precursor includes secondary particles composed of primary particles, and the particle size D50 of the secondary particles is 6 to 25 μm; the surface of the secondary particles is porous, and the average cross-sectional porosity is 25 to 55%; the secondary particles include an inner core layer and an outer shell layer along the radial direction, and the cross-sectional porosity of the inner core layer of the secondary particles is less than the cross-sectional porosity of the outer shell layer. The surface of the positive electrode material precursor of the present application is porous, and the cross-section also has a high porosity, indicating that the precursor material is porous as a whole.
[0007] Through the optimization design of the morphology of the positive electrode material precursor, the positive electrode material precursor is a hydroxide containing a transition metal, including secondary particles composed of primary particles, wherein the secondary particles of the positive electrode material precursor are porous as a whole, and the secondary particle size D50 is 6 to 25 μm. The positive electrode material precursor has a porous structure and a larger particle size, which is beneficial to reduce the particle interface that lithium ions need to pass through when migrating during the charging and discharging process of the positive electrode material, so that the interface resistance of the positive electrode material is reduced, thereby improving the electron mobility and effectively improving the battery capacity.
[0008] In addition, the average cross-sectional porosity of the secondary particles is 25-55%. The secondary particles have a larger average cross-sectional porosity, which is beneficial to promoting the sintering mass transfer process in the process of sintering the positive electrode material precursor into the positive electrode material, reducing the sintering temperature required for the positive electrode material, reducing the sintering cost, and inhibiting the destruction of the crystal structure caused by high-temperature sintering, so as to maintain the consistency of the crystal structure of the positive electrode material and improve the cycle performance and safety performance of the battery; the larger average cross-sectional porosity is also beneficial to the full infiltration of the electrolyte during the charging and discharging process of the positive electrode material, so as to provide more active sites for electronic reaction, thereby further improving the electron conduction rate and improving the capacity and rate performance of the battery.
[0009] In addition, the secondary particles are divided into an inner core layer and an outer shell layer along the radial direction. The inner core layer has a smaller cross-sectional porosity, while the outer shell layer has a larger cross-sectional porosity. The smaller cross-sectional porosity of the inner core layer is beneficial to improving the stability of the internal structure of the secondary particles, thereby further improving the battery cycle performance, while the larger cross-sectional porosity of the outer shell layer is more conducive to the rapid migration of electrons and sufficient infiltration of the electrolyte, thereby further significantly improving the battery's capacity and rate performance.
[0010] In some embodiments, the cathode material precursor is a nickel-containing hydroxide, the molar content of nickel in the cathode material precursor accounts for ≥50% of the total metal molar content; preferably ≥75%; and / or the specific surface area of the secondary particles is 45 to 100 m 2 / g.
[0011] In some embodiments, the cathode material precursor satisfies at least one of the following conditions:
[0012] (1) The outer shell surface of the secondary particles presents a honeycomb-like pore structure;
[0013] (2) The pore diameter of the inner core layer of the secondary particles is smaller than the pore diameter of the outer shell layer;
[0014] (3) The average pore diameter of the secondary particles is 200-600 nm;
[0015] (4) The ratio of the pore diameter of the inner core layer to the pore diameter of the outer shell layer of the secondary particles is 0.30 to 0.80;
[0016] (5) The ratio of the cross-sectional porosity of the inner core layer of the secondary particles to the cross-sectional porosity of the outer shell layer is 0.15 to 0.50.
[0017] In some embodiments, the cathode material precursor satisfies at least one of the following conditions:
[0018] A. The particle size D50 of the secondary particles is 8 to 20 μm;
[0019] B. The particle size distribution Span value of the secondary particles is 0.18 to 1.5, preferably 0.2 to 0.4;
[0020] C. The specific surface area of secondary particles is 50-100m 2 / g, preferably 55-87m 2 / g;
[0021] D. The surface density of secondary particles is 35-85%;
[0022] E. The average pore diameter of the secondary particles is 400-600 nm;
[0023] F. The sphericity of secondary particles is 80-100%;
[0024] G. The percentage of nickel molar content in the positive electrode material precursor to the total metal molar content is ≥ 75%;
[0025] I. The primary particles are in flake form;
[0026] J. The thickness of the primary particles is 3 to 33 nm;
[0027] In some embodiments, the chemical formula of the cathode material precursor is Ni a Co b Mn c Me (1-a-b-c) (OH)2, wherein 0.50≤a≤1.00, 0≤b≤0.50, 0≤c≤0.50, 0.90≤a+b+c≤1.00, and Me is a doping element; optionally, Me includes at least one of B, P, Ti, Y, Zr, Ca, Nb, Mg, Al, W or La.
[0028] The second aspect of the present application provides a method for preparing the positive electrode material precursor as described above, comprising:
[0029] Preparing a metal salt solution, a precipitant solution and a complexing agent solution, and mixing the solvent, the precipitant solution and the complexing agent solution to obtain a base solution;
[0030] A metal salt solution, a precipitant solution and a complexing agent solution are simultaneously introduced into the base liquid to carry out a synthesis reaction to obtain a hydroxide slurry;
[0031] The hydroxide slurry is post-treated to obtain a positive electrode material precursor.
[0032] In some embodiments, the preparation method selects one or more of the following conditions:
[0033] a. The synthesis reaction comprises: simultaneously introducing a metal salt solution, a precipitant solution and a complexing agent solution into a base liquid to carry out a first coprecipitation reaction to obtain a hydroxide slurry; or simultaneously introducing a metal salt solution, a precipitant solution and a complexing agent solution into a base liquid to carry out a first coprecipitation reaction, after obtaining a seed crystal of a target particle size through reaction, the seed crystal is mixed with the metal salt solution, the precipitant solution and the complexing agent solution to obtain a reaction liquid, and the metal salt solution, the precipitant solution and the complexing agent solution are introduced into the reaction liquid to carry out a second coprecipitation reaction to obtain a hydroxide slurry;
[0034] b. Post-treatment includes: sequentially performing solid-liquid separation, washing, drying and screening on the hydroxide slurry to obtain a positive electrode material precursor;
[0035] c. The raw materials of the metal salt solution include: nickel salt, cobalt salt, manganese salt and a combination of doped metal salts containing at least nickel salt;
[0036] d. The precipitant includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate;
[0037] e. The complexing agent includes at least one of ammonia water, ammonium bicarbonate, ammonium carbonate, citric acid, sodium citrate, ammonium citrate, oxalic acid or ammonium oxalate;
[0038] f. The total mass concentration of metal ions in the metal salt solution is 60-150 g / L;
[0039] g. The solute mass fraction of the precipitant solution is 5.0 to 50.0 wt %;
[0040] h. The solute mass fraction of the complexing agent solution is 0.5 to 50.5 wt %;
[0041] i. The pH of the base solution is 10.00-12.00;
[0042] j. The concentration of the complexing agent in the base solution is 4.0-15.0 g / L;
[0043] k. The temperature of the base liquid is 45-80°C;
[0044] 1. During the synthesis reaction, the feed rate of the metal salt solution is 1.00-10.00% / h of the reaction vessel volume;
[0045] m. During the synthesis reaction, the feed rate of the precipitant solution is 0.30-10.30% / h of the volume of the reaction vessel;
[0046] n. During the synthesis reaction, the feeding rate of the complexing agent solution is 0.01-0.90% / h of the reaction vessel volume;
[0047] o. During the synthesis reaction, the concentration of the complexing agent in the reaction system is 0.5-20.0 g / L;
[0048] p. During the synthesis reaction, the pH value of the reaction system is 9.50-11.50;
[0049] q. The synthesis reaction is carried out under stirring conditions, and the stirring speed is 50 to 1500 r / min;
[0050] r. The reaction temperature of the synthesis reaction is 45-80°C.
[0051] A third aspect of the present application provides a positive electrode material, wherein the raw material of the positive electrode material includes the positive electrode material precursor as described above or the positive electrode material precursor prepared by the above preparation method.
[0052] A fourth aspect of the present application provides a battery, comprising an electrode made of the positive electrode material as described above.
[0053] A fifth aspect of the present application provides an electrical device, comprising the battery as described above. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0055] Figure 1 This is a SEM image (1000 times) of the cathode material precursor prepared in Example 1 of the present application;
[0056] Figure 2 This is a SEM image (5000 times) of the cathode material precursor prepared in Example 1 of the present application;
[0057] Figure 3 This is a SEM image (50,000 times) of the cathode material precursor prepared in Example 1 of the present application;
[0058] Figure 4 This is a cross-sectional view of the positive electrode material precursor CP prepared in Example 1 of the present application;
[0059] Figure 5 This is a SEM image (1000 times) of the cathode material precursor prepared in Example 2 of the present application;
[0060] Figure 6 This is a SEM image (5000 times) of the cathode material precursor prepared in Example 2 of the present application;
[0061] Figure 7 This is a SEM image (50,000 times) of the cathode material precursor prepared in Example 2 of the present application;
[0062] Figure 8 This is a cross-sectional view of the positive electrode material precursor CP prepared in Example 2 of the present application;
[0063] Fig. 9 This is a SEM image (1000 times) of the positive electrode material precursor prepared in Comparative Example 1 of the present application;
[0064] Fig.10 This is a SEM image (5000 times) of the positive electrode material precursor prepared in Comparative Example 1 of the present application;
[0065] Fig.11 This is a SEM image (50,000 times) of the positive electrode material precursor prepared in Comparative Example 1 of the present application;
[0066] Fig.12 This is a cross-sectional view of the positive electrode material precursor CP prepared in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0067] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0068] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0069] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0070] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0071] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0072] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0073] It should be noted that the "primary particles" in this application refer to the smallest unit in the cathode material precursor without stacking, flocculation and other structures, that is, the original, unagglomerated single particles, usually fine crystals directly generated by chemical reactions (such as coprecipitation reactions). The "secondary particles" in this application refer to particles formed by the combination of multiple primary particles in the cathode material precursor.
[0074] It should be noted that the "cross-sectional porosity" in the embodiment of the present application is a parameter that characterizes the cross-sectional morphology of the particles, that is, the percentage of pores in the cross-sectional view (i.e., CP cross-sectional view) to the overall volume. For example, for the average cross-sectional porosity of the secondary particles in the embodiment of the present application, the measurement method can be: take several (such as 5) CP cross-sectional views of the secondary particles of the positive electrode material precursor, and select multiple (≥10) regions in each CP cross-sectional view for cross-sectional porosity calculation, and the calculation formula is: cross-sectional porosity = regional pore area / regional total area × 100%, thereby obtaining the average cross-sectional porosity of multiple regions in a single CP cross-sectional view, and then averaging the average cross-sectional porosity of multiple CP cross-sectional views as the final average cross-sectional porosity; wherein the CP cross-sectional view is a SEM view of the cross section of the secondary particles taken using a field emission scanning electron microscope (HITACHI SU8100) (such as a magnification of 4500 times, a magnification of 5000 times, etc.), and the region is a partial cross-section in the SEM view selected using ImageJ software.
[0075] It should be noted that the "inner core layer" and "outer shell layer" in the embodiments of the present application are divided according to the radial direction of the secondary particles of the positive electrode material precursor. The inner core layer is located inside the secondary particles and is the core part of the secondary particles, while the outer shell layer is located outside the secondary particles and is closely connected with the inner core layer.
[0076] An embodiment of the present application provides a positive electrode material precursor, which is a hydroxide containing a transition metal. The positive electrode material precursor includes secondary particles composed of primary particles, and the particle size D50 of the secondary particles is 6 to 25 μm; the surface of the secondary particles is porous, and the average cross-sectional porosity is 25 to 55%; the secondary particles include an inner core layer and an outer shell layer along the radial direction, and the cross-sectional porosity of the inner core layer of the secondary particles is less than the cross-sectional porosity of the outer shell layer.
[0077] It can be understood that the surface of the positive electrode material precursor is porous and the cross-section also has a high porosity, indicating that the precursor material is porous as a whole. The embodiment of the present application designs the morphology of the positive electrode material precursor. The positive electrode material precursor includes secondary particles composed of primary particles, wherein the secondary particles have a porous structure and the particle size D50 of the secondary particles is 6 to 25 μm. The positive electrode material precursor has a porous structure and a larger particle size, which is beneficial to reducing the particle interface that lithium ions need to pass through when migrating during the charging and discharging process of the positive electrode material, thereby improving the electron mobility and promoting the battery capacity to be improved.
[0078] Furthermore, the average cross-sectional porosity of the secondary particles is 25-55%, and the cathode material precursor is porous and loose as a whole, with a large average cross-sectional porosity, which is beneficial to promote the sintering mass transfer process when preparing the cathode material, reduce the sintering temperature of the cathode material, and thus reduce the sintering cost, and inhibit the destruction of the crystal structure of the cathode material caused by high-temperature sintering to maintain the consistency of the crystal structure, thereby improving the battery cycle performance and safety performance; at the same time, the large average cross-sectional porosity is also beneficial to promote the full infiltration of the electrolyte during the charging and discharging process of the cathode material to provide more active sites for electron reaction, thereby further increasing the electron transfer rate and improving the capacity and rate performance of the battery.
[0079] What is particularly critical is that the secondary particles in the embodiments of the present application adopt a layered design. The secondary particles are divided into an inner core layer and an outer shell layer in the radial direction. The inner core layer has a smaller cross-sectional porosity, and the outer shell layer has a larger cross-sectional porosity. The outer shell layer is looser than the inner core layer. The smaller cross-sectional porosity of the inner core layer is beneficial to improving the stability of the internal structure of the secondary particles, thereby further improving the battery cycle performance, while the larger cross-sectional porosity of the outer shell layer is more conducive to the rapid migration of electrons and sufficient infiltration of the electrolyte, thereby further significantly improving the battery capacity and rate performance.
[0080] The cathode material precursor provided in the embodiment of the present application is a hydroxide containing a transition metal. For example, the cathode material precursor may be a hydroxide containing a transition metal element such as nickel, cobalt, and manganese.
[0081] In the embodiment of the present application, the cathode material precursor includes secondary particles composed of primary particles, and the particle size D50 of the secondary particles is 6 to 25 μm. For example, the particle size D50 of the secondary particles can be 6.00 μm, 6.50 μm, 7.00 μm, 7.50 μm, 8.00 μm, 8.50 μm, 9.00 μm, 9.50 μm, 10.00 μm, 10.50 μm, 11.00 μm, 11.50 μm, 12.00 μm, 12.50 μm, 13.00 μm, 13.50 μm, 14.00 μm, 15.00 μm, 16.00 μm, 17.00 μm, 18.00 μm, 19.00 μm, 20.00 μm, 21.00 μm, 22.00 μm, 23.00 μm, 24.00 μm, 25.00 μm, 26.00 μm, 27.00 μm, 28.00 μm, 29.00 μm, 30.00 μm, 31.00 μm, 32.00 μm, 33.00 μm, 34.00 μm, 35.00 μm, 36.00 μm, 37.00 μm, 38.00 μm, 39.00 μm, 40.00 μm, 41.00 μm, 42.00 μm, 43.00 μm, 44.00 μm, 45.00 μm, 46.00 μm, 47.00 μm, 48.00 μm, 49. The particle size D50 can be 4.50μm, 15.00μm, 15.50μm, 16.00μm, 16.50μm, 17.00μm, 17.50μm, 18.00μm, 18.50μm, 19.00μm, 19.50μm, 20.00μm, 20.50μm, 21.00μm, 21.50μm, 22.00μm, 22.50μm, 23.00μm, 23.50μm, 24.00μm, 24.50μm, 25.00μm or any particle size D50 in the range of 6 to 25μm.
[0082] The secondary particles in the embodiments of the present application have a porous structure and an average cross-sectional porosity of 25-55%. For example, the average cross-sectional porosity of the secondary particles can be 25.0%, 25.5%, 26.0%, 26.5%, 27.0%, 27.5%, 28.0%, 28.5%, 29.0%, 29.5%, 30.0%, 30.5%, 31.0%, 31.5%, 32.0%, 32.5%, 33.0%, 33.5%, 34.0%, 34.5%, 35.0%, 35.5%, 36.0%, 36.5%, 37.0%, 37.5%, 38.0%, 38.5%, 39.0%, 40.0%, 41.0%, 42.0%, 43.0%, 44.0%, 45.0%, 46.0%, 47.0%, 48.0%, 49.0%, 50.0%, 51.0%, 52.0%, 53.0%, 54.0%, 55.0%, 56.0%, 57.0%, 58.0%, 59 ... %, 39.0%, 39.5%, 40.0%, 40.5%, 41.0%, 41.5%, 42.0%, 42.5%, 43.0%, 43.5%, 44.0%, 44.5%, 45.0%, 45.5%, 46.0%, 46.5%, 47.0%, 47.5%, 48.0%, 48.5%, 49.0%, 49.5%, 50.0%, 50.5%, 51.0%, 51.5%, 52.0%, 52.5%, 53.0%, 53.5%, 54.0%, 54.5%, 55.0%, or any average cross-sectional porosity in the range of 25 to 55%.
[0083] In some embodiments, the cathode material precursor is a nickel-containing hydroxide, and the molar content of nickel in the cathode material precursor accounts for ≥50% of the total molar content of metals; the BET specific surface area of the secondary particles is 45 to 100 m 2 / g.
[0084] The positive electrode material precursor in the embodiment of the present application is a nickel-containing hydroxide, and the nickel molar content accounts for ≥50% of the total metal molar content. The hydroxide with a medium to high nickel content as a positive electrode material precursor is beneficial to improving the energy density and discharge specific capacity of the positive electrode material; at the same time, the specific surface area BET of the secondary particles is 45 to 100 m 2 / g, the secondary particles have a larger particle size and more porous structure, and further have a larger specific surface area, which is beneficial for the active substances (such as nickel) inside the positive electrode material particles to exert their capacity advantages, thereby improving the utilization efficiency of the active substances and further improving the battery capacity.
[0085] In some embodiments, the surface of the outer shell layer of the secondary particle has a honeycomb-like pore structure.
[0086] It should be noted that the honeycomb-like pore structure in the embodiment of the present application refers to the pores on the surface of the outer shell layer of the secondary particles being interconnected in the form of hexagons or polygons to form a complex network similar to a honeycomb. The honeycomb-like pore structure on the surface of the outer shell layer of the secondary particles is beneficial to causing the outer shell layer of the secondary particles to have a higher porosity, and the pores in the outer shell layer of the secondary particles have a larger pore diameter size, making the surface of the outer shell layer rougher, so as to reduce the contact angle of the positive electrode material with the electrolyte during the charging and discharging process, improve the wettability of the electrolyte, thereby promoting the charging and discharging performance of the positive electrode material and the battery capacity to be further improved.
[0087] In some embodiments, the average pore diameter of the secondary particles is 200-600 nm. For example, the average pore diameter of the secondary particles can be 200 nm, 210 nm, 220 nm, 230 nm, 240 nm, 250 nm, 260 nm, 270 nm, 280 nm, 290 nm, 300 nm, 300 nm, 310 nm, 320 nm, 330 nm, 340 nm, 350 nm, 360 nm, 370 nm, 380 nm, 390 nm, 400 nm, 410 nm, 420 nm, 430 nm, 440 nm, 450 nm, 460 nm, 470 nm, 480 nm, 490 nm, 500 nm, 510 nm, 520 nm, 530 nm, 540 nm, 550 nm, 560 nm, 570 nm, 580 nm, 590 nm, 600 nm, 610 nm, 620 nm, 630 nm, 640 nm, 650 nm, 660 nm, 670 nm, 680 nm, 690 nm, 700 nm, 710 nm, 720 nm, 730 nm, 740 nm, 750 nm, 760 nm, 770 nm, 780 nm, 790 nm, 800 nm, 810 nm, 820 nm, 830 nm, 840 nm, 850 nm, 860 nm, 870 nm, 880 nm, 890 nm, 900 nm, 910 nm, 920 nm, 930 nm, 940 nm, 950 nm, 960 nm, 970 nm 0nm, 390nm, 400nm, 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm, 500nm, 510nm, 520nm, 530nm, 540nm, 550nm, 560nm, 570nm, 580nm, 590nm, 600nm, or any average pore diameter in the range of 200 to 600nm.
[0088] The secondary particles in the embodiments of the present application not only have a higher average cross-sectional porosity, but also have a larger diameter size of pores. The secondary particles as a whole can be porous and loose, which is beneficial to reduce the interface impedance of the positive electrode material, promote the sintering mass transfer process in the preparation process of the positive electrode material, and enhance the wettability of the electrolyte during the charging and discharging process of the positive electrode material, thereby effectively improving the cycle performance, rate performance and capacity of the battery.
[0089] In some embodiments, the pore diameter of the inner core layer of the secondary particles is smaller than the pore diameter of the outer shell layer, the cross-sectional porosity of the inner core layer of the secondary particles is smaller than the cross-sectional porosity of the outer shell layer, and the pore diameter of the inner core layer is smaller than the pore diameter of the outer shell layer, and the pore arrangement of the secondary particles tends to increase from the inside to the outside, that is, the cross-sectional porosity and pore diameter of the secondary particles appear to be large on the outside and small on the inside. The smaller cross-sectional porosity and pore diameter of the inner core layer are more conducive to improving the stability of the positive electrode material, so as to improve the cycle performance, while the larger cross-sectional porosity and pore diameter of the outer shell layer are conducive to the rapid migration of electrons and sufficient infiltration of the electrolyte, so as to improve the battery capacity and rate performance.
[0090] In some embodiments, the particle size D50 of the secondary particles is 8 to 20 μm. When the particle size D50 of the secondary particles is within this range, the positive electrode material precursor has a porous structure and an appropriate particle size, so as to reduce the particle interface that lithium ions need to pass through when migrating during the charging and discharging process of the positive electrode material, thereby improving the electron mobility and effectively improving the battery capacity.
[0091] In some embodiments, the particle size distribution Span value of the secondary particles is 0.18-1.5, preferably 0.2-0.4; the secondary particles of the positive electrode material precursor have a smaller particle size distribution Span value, and the particle size is more uniform, which is conducive to the close stacking of the positive electrode material, thereby improving the cycle stability and rate performance of the battery.
[0092] It should be noted that the "Span value" in the examples of the present application is used to characterize the secondary particle size distribution, using the formula Span = (D 90 -D 10 ) / D 50 Calculated, where D 90 , D 10 , D 50 They respectively represent the particle sizes corresponding to 10%, 50%, and 90% of the particles in the particle size distribution. The smaller the Span value, the more concentrated the particle size distribution is, that is, the more uniform the particle size is.
[0093] In some embodiments, the BET specific surface area of the secondary particles is 50 to 100 m 2 / g. Within this range, the secondary particles have a larger particle size, more porous structure and a larger specific surface area, so as to give full play to the capacity advantage of the active substances (such as nickel) inside the positive electrode material particles, improve the utilization efficiency of the active substances, and effectively improve the battery capacity.
[0094] In some embodiments, the BET specific surface area of the secondary particles is 55 to 87 m 2 / g. Within this range, the secondary particles have a larger particle size, more porous structure and a larger specific surface area, so as to further exert the capacity advantage of the active substances (such as nickel) inside the positive electrode material particles, improve the utilization efficiency of the active substances, and effectively increase the battery capacity.
[0095] In some embodiments, the surface density of the secondary particles is 35-85%. Within this range, the surface of the outer shell layer of the secondary particles has a relatively large porous structure, which is beneficial for reducing the contact angle between the positive electrode material and the electrolyte during the charging and discharging process and improving the wettability of the electrolyte, thereby further improving the charging and discharging performance of the positive electrode material and the battery capacity.
[0096] It should be noted that the "surface density" in the embodiments of the present application is a parameter that characterizes the surface morphology of the secondary particles. For example, the surface density can be measured by taking multiple (such as 5) SEM images of the positive electrode material precursor at a certain magnification (such as 5000 times) through a field emission scanning electron microscope (HITACHISU8100), and using the calculation formula: surface density = 100% - surface porosity, analyzing the surface density in each SEM image, and then taking the surface density of several (such as 5) SEM images and taking the average value as the final surface density.
[0097] In some embodiments, the average pore diameter of the secondary particles is 400-600 nm. The pore size of the secondary particles is larger, which is more conducive to the rapid migration of electrons and promotes the sintering mass transfer process during the preparation of the positive electrode material, thereby effectively improving the battery cycle performance, capacity and rate performance.
[0098] In some embodiments, the sphericity of the secondary particles is 80-100%. The secondary particles have a high sphericity, which is beneficial to improving the structural stability of the positive electrode material particles and promoting the improvement of the cycle stability of the battery.
[0099] It should be noted that the "sphericity" in this application is a parameter that characterizes the morphology of secondary particles. For example, the method for measuring the sphericity can be: using a field emission scanning electron microscope (HITACHI SU8100) to take multiple (such as 5) SEM images of a certain magnification (such as 3000 times) of the positive electrode material precursor, and using the sphericity software Avizo through the calculation formula: Sphericity = (4π×area) / (circumference×circumference)×100%, analyze the sphericity in each SEM image, and then take the sphericity of several (such as 5) SEM images and take the average value as the final sphericity.
[0100] In some embodiments, the nickel molar content in the positive electrode material precursor accounts for ≥75% of the total metal molar content, and the positive electrode material precursor has a higher nickel content, which is beneficial to further improve the energy density and discharge specific capacity of the positive electrode material.
[0101] In some embodiments, the ratio of the pore diameter of the inner core layer to the pore diameter of the outer shell layer of the secondary particles is 0.30 to 0.80. Within this range, the pore diameter of the inner core layer is smaller than that of the outer shell layer, and the pore diameter of the inner core layer is larger. The inner core layer is slightly dense, while the pore diameter of the outer shell layer is smaller and relatively loose, so as to take into account the structural stability of the positive electrode material particles, thereby improving the cycle performance of the positive electrode material, and at the same time enabling electrons to have a faster migration rate and ensure sufficient infiltration of the electrolyte, thereby improving the capacity performance and rate performance of the positive electrode material.
[0102] In some embodiments, the ratio of the cross-sectional porosity of the inner core layer of the secondary particles to the cross-sectional porosity of the outer shell layer is 0.15 to 0.50. Within this range, the cross-sectional porosity of the inner core layer is smaller than that of the outer shell layer. The inner core layer has fewer pores and is slightly denser, while the outer shell layer has more pores and is relatively looser, so as to take into account the structural stability of the positive electrode material particles, thereby improving the cycle performance of the positive electrode material, and at the same time enabling electrons to have a faster migration rate and ensure sufficient infiltration of the electrolyte, thereby improving the capacity performance and rate performance of the positive electrode material.
[0103] In some embodiments, the primary particles are in the form of flakes, and the thickness of the primary particles is 3 to 33 nm. That is to say, the thickness of the primary particles is much smaller than other dimensions. The thickness of the primary particles is 3 to 33 nm, which is more conducive to the secondary particles obtaining a larger specific surface area and shortening the lithium ion migration path, thereby improving the battery capacity, cycle performance and rate performance.
[0104] It should be noted that in order to characterize the pore diameter of the secondary particles and the thickness parameters of the primary particles in the embodiments of the present application, the Nano Measurer software can be used to measure the diameter of the pores on the surface of the secondary particles and the thickness of the primary particles in the SEM image of a certain magnification (such as 50,000 times), and at least 10 sets of data are taken, and then the average value is taken to obtain the average pore diameter of the secondary particles and the thickness of the primary particles.
[0105] It should be clear that the physical and chemical parameters (such as porosity) of the inner core layer and outer shell layer of the secondary particles of the positive electrode material precursor in the embodiment of the present application are measured based on the layered relationship that the inner core layer diameter accounts for 60% of the overall diameter of a single secondary particle, and the remaining 40% is the outer shell layer.
[0106] In some embodiments, the chemical formula of the cathode material precursor is Ni a Co b Mn c Me (1-a-b-c) (OH)2, wherein 0.50≤a≤1.00, 0≤b≤0.50, 0≤c≤0.50, 0.90≤a+b+c≤1.00, and Me is a doping element; optionally, Me includes at least one of B, P, Ti, Y, Zr, Ca, Nb, Mg, Al, W or La.
[0107] It can be understood that the positive electrode material precursor provided in the embodiment of the present application can be a pure phase nickel cobalt manganese hydroxide, or it can be a nickel cobalt manganese hydroxide doped with elements such as B, P, Ti, Y, Zr, Ca, Nb, Mg, Al, W or La. By introducing suitable doping elements into the positive electrode material precursor, the electrical performance of the battery can be further improved.
[0108] Another embodiment of the present application provides a method for preparing the positive electrode material precursor as described above, comprising:
[0109] Preparing a metal salt solution, a precipitant solution and a complexing agent solution, and mixing the solvent, the precipitant solution and the complexing agent solution to obtain a base solution;
[0110] A metal salt solution, a precipitant solution and a complexing agent solution are simultaneously introduced into the base liquid to carry out a synthesis reaction to obtain a hydroxide slurry;
[0111] The hydroxide slurry is post-treated to obtain a positive electrode material precursor.
[0112] In the embodiment of the present application, by presetting the pH value, temperature and complexing agent concentration of the base liquid, and controlling the parameters such as the feed rate of the metal salt solution, the precipitant solution and the complexing agent solution, the pH value of the reaction system during the synthesis reaction, the synthesis process of the positive electrode material precursor can be finely regulated, so that the prepared positive electrode material precursor secondary particles have a porous structure, a larger particle size D50 and an average cross-sectional porosity, and the positive electrode material precursor secondary particles are layered inside and outside, and the cross-sectional porosity of the inner core layer is smaller than the cross-sectional porosity of the outer shell layer, so as to improve the battery capacity, rate performance and cycle performance.
[0113] In the embodiment of the present application, the solvent may be pure water, that is, H2O without impurities.
[0114] In some embodiments, the synthesis reaction specifically includes: simultaneously introducing a metal salt solution, a precipitant solution and a complexing agent solution into a base liquid to carry out a first co-precipitation reaction to obtain a hydroxide slurry; or, simultaneously introducing a metal salt solution, a precipitant solution and a complexing agent solution into a base liquid to carry out a first co-precipitation reaction, after obtaining target particle size seed crystals by reaction, the seed crystals are mixed with the metal salt solution, the precipitant solution and the complexing agent solution to obtain a reaction liquid, and the metal salt solution, the precipitant solution and the complexing agent solution are introduced into the reaction liquid to carry out a second co-precipitation reaction to obtain a hydroxide slurry.
[0115] The hydroxide slurry in the embodiment of the present application can be made by a single co-precipitation reaction or by a staged co-precipitation reaction. The staged co-precipitation reaction is more conducive to achieving fine control of the crystal growth process, so as to obtain a positive electrode material precursor with a more ideal morphology.
[0116] In some embodiments, the post-processing specifically includes: sequentially performing solid-liquid separation, washing, drying and screening on the hydroxide slurry to obtain a positive electrode material precursor.
[0117] In the embodiment of the present application, by sequentially subjecting the hydroxide slurry to solid-liquid separation, washing, drying and screening, impurities in the positive electrode material precursor can be effectively removed, so as to obtain a high-quality positive electrode material precursor product that meets the specification requirements.
[0118] In some embodiments, the raw materials of the metal salt solution include: nickel salt, cobalt salt, manganese salt and various combinations of doped metal salts including at least nickel salt.
[0119] In some embodiments, the precipitant includes at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate.
[0120] In some embodiments, the complexing agent includes at least one of ammonia, ammonium bicarbonate, ammonium carbonate, citric acid, sodium citrate, ammonium citrate, oxalic acid or ammonium oxalate.
[0121] In some embodiments, the total mass concentration of metal ions in the metal salt solution is 60-150 g / L; the mass fraction of solute in the precipitant solution is 5.0-50.0 wt %; and the mass fraction of solute in the complexing agent solution is 0.5-50.5 wt %.
[0122] In some embodiments, the pH of the base solution is 10.00-12.00; the concentration of the complexing agent in the base solution is 4.0-15.0 g / L; and the temperature of the base solution is 45-80°C.
[0123] In some embodiments, during the synthesis reaction, the feed rate of the metal salt solution is 1.00-10.00% / h of the reaction container volume; the feed rate of the precipitant solution is 0.30-10.30% / h of the reaction container volume; and the feed rate of the complexing agent solution is 0.01-0.90% / h of the reaction container volume.
[0124] In some embodiments, during the synthesis reaction, the concentration of the complexing agent in the reaction system is 0.5-20.0 g / L; and the pH value of the reaction system is 9.50-11.50.
[0125] In some embodiments, the synthesis reaction is carried out under stirring conditions, and the stirring speed is 50-1500 r / min; the reaction temperature of the synthesis reaction is 45-80°C.
[0126] Another embodiment of the present application provides a positive electrode material, wherein the raw material of the positive electrode material includes the positive electrode material precursor as described above or the positive electrode material precursor prepared by the above preparation method.
[0127] The positive electrode material in the embodiment of the present application can be prepared by sintering the above-mentioned positive electrode material precursor and a lithium source. Since the secondary particles of the positive electrode material precursor have a large average cross-sectional porosity, the sintering process of the positive electrode material can have a sintering temperature below 700°, thereby reducing the sintering cost, which is beneficial to inhibiting the destruction of the crystal structure of the positive electrode material caused by high-temperature sintering, maintaining the consistency of the crystal structure, and further improving the battery cycle performance and safety performance.
[0128] Another embodiment of the present application provides a battery, which includes an electrode made of the positive electrode material as described above.
[0129] The battery in the embodiment of the present application may be a lithium-ion battery, and the electrode included in the lithium-ion battery may be a positive electrode sheet made by mixing the above-mentioned positive electrode material with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a predetermined ratio into a slurry, which is then coated on a current collector.
[0130] Another embodiment of the present application provides an electrical device, including the battery as described above.
[0131] The following examples describe the disclosure of the present application in more detail, and these examples are merely illustrative, as it will be apparent to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all reagents and raw materials used in the examples are commercially available or synthesized according to conventional methods, and the instruments used in the examples are commercially available.
[0132] Example 1
[0133] (1) Preparation of cathode material precursor:
[0134] The positive electrode material precursor prepared in this embodiment has the chemical formula Ni 0.96 Co 0.03 Mn 0.01 (OH)2, the preparation process is as follows:
[0135] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=96:3:1; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0136] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.50, the ammonia concentration is maintained at 5.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min. After the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0137] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.00, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out. By fine-tuning the feed rate of solution B and solution C, the reaction solution was heated to 50° C. and stirred at a constant temperature. The pH value of the reaction system is controlled to be 10.05-10.15 and the ammonia concentration is 4.6-5.4 g / L by adjusting the feed rate of liquid C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seed crystals are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 of the particles grows stably to 10.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.96 Co 0.03 Mn 0.01 (OH)2 cathode material precursor.
[0138] (2) Preparation of positive electrode materials
[0139] The positive electrode material precursor prepared in this embodiment was mixed evenly with lithium hydroxide in a ratio of 1:1.08, and then sintered at 600° C. for 10 h to obtain a positive electrode material.
[0140] Example 2
[0141] (1) Preparation of cathode material precursor:
[0142] The positive electrode material precursor prepared in this embodiment has the chemical formula Ni 0.96 Co 0.03 Mn 0.01 (OH)2, the preparation process is as follows:
[0143] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=96:3:1; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0144] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.50, the ammonia concentration is maintained at 5.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min. After the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0145] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.00, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out. By fine-tuning the feed rate of solution B and solution C, the reaction solution was heated to 50° C. and stirred at a constant temperature. The pH value of the reaction system is controlled to be 10.25-10.35 and the ammonia concentration is 4.6-5.4 g / L by adjusting the feed rate of liquid C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seeds are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 of the particles grows stably to 10.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.96 Co 0.03 Mn 0.01 (OH)2 cathode material precursor.
[0146] (2) Preparation of positive electrode materials
[0147] The positive electrode material precursor prepared in this embodiment was mixed evenly with lithium hydroxide in a ratio of 1:1.08, and then sintered at 650° C. for 10 h to obtain a positive electrode material.
[0148] Example 3
[0149] (1) Preparation of cathode material precursor:
[0150] The positive electrode material precursor prepared in this embodiment has the chemical formula Ni 0.70 Co 0.10 Mn 0.20 (OH)2, the preparation process is as follows:
[0151] A metal salt solution with a total metal ion mass concentration of 121 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=70:10:20; a sodium hydroxide solution with a solute mass fraction of 19.9 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 15.7 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.55, the mass concentration of ammonia solution was controlled to be 4.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 47°C.
[0152] Solution A, solution B and solution C are simultaneously introduced into the bottom liquid in the reaction container, and a first coprecipitation reaction is carried out under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 8.0% / h, 6.0% / h and 0.18% / h of the volume of the reaction container, respectively. During the reaction, the pH of the reaction system is controlled to be maintained at 9.90-10.00, and the stirring device is controlled to stir at a speed of 200.35 r / min. During the reaction, the stirring is reduced by 20-25 r / min every 10 hours, and the final stirring is maintained at 66.3 r / min until the particle size D50 of the particles grows stably to 14.0±0.3 μm, thereby obtaining a hydroxide slurry, and the hydroxide slurry is solid-liquid separated to obtain a precipitate, and the precipitate is washed, dried and sieved to obtain a chemical formula of Ni 0.70 Co 0.10 Mn 0.20 (OH)2 cathode material precursor.
[0153] (2) Preparation of positive electrode materials
[0154] The positive electrode material precursor prepared in this embodiment was mixed evenly with lithium hydroxide in a ratio of 1:1.08, and then sintered at 550° C. for 10 hours to obtain a positive electrode material.
[0155] Example 4
[0156] (1) Preparation of cathode material precursor:
[0157] The positive electrode material precursor prepared in this embodiment has the chemical formula Ni 0.96 Co 0.03Mn 0.01 (OH)2, the preparation process is as follows:
[0158] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=96:3:1; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0159] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.50, the ammonia concentration is maintained at 5.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min. After the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0160] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.00, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out, and the reaction mixture was finely adjusted by adjusting the feed rate of solution B and solution C. The pH value of the reaction system is controlled to be 9.55-9.65 and the ammonia concentration is 4.6-5.4 g / L by adjusting the feeding rate of solution C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seed crystals are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 of the particles grows stably to 10.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.96 Co 0.03 Mn 0.01 (OH)2 cathode material precursor.
[0161] (2) Preparation of positive electrode materials
[0162] The positive electrode material precursor prepared in this embodiment was mixed evenly with lithium hydroxide in a ratio of 1:1.08, and then sintered at 540° C. for 10 hours to obtain a positive electrode material.
[0163] Example 5
[0164] (1) Preparation of cathode material precursor:
[0165] The positive electrode material precursor prepared in this embodiment has the chemical formula Ni 0.95 Co 0.03 Mn 0.01 Al 0.01 (OH)2, the preparation process is as follows:
[0166] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate, manganese sulfate and aluminum sulfate, and the molar ratio of nickel, cobalt, manganese and aluminum was Ni:Co:Mn:Al=95:3:1:1; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0167] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.50, the ammonia concentration is maintained at 5.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min. After the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0168] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.00, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out. By fine-tuning the feed rate of solution B and solution C, the reaction solution was heated to 50° C. and stirred at a constant temperature. The pH value of the reaction system is controlled to be 10.05-10.15 and the ammonia concentration is 4.6-5.4 g / L by adjusting the feed rate of liquid C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seed crystals are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 of the particles grows stably to 10.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.95 Co 0.03 Mn 0.01 Al 0.01 (OH)2 cathode material precursor.
[0169] (2) Preparation of positive electrode materials
[0170] The positive electrode material precursor prepared in this embodiment was mixed evenly with lithium hydroxide in a ratio of 1:1.08, and then sintered at 700° C. for 10 hours to obtain a positive electrode material.
[0171] Example 6
[0172] (1) Preparation of cathode material precursor:
[0173] The positive electrode material precursor prepared in this embodiment has the chemical formula Ni 0.96 Co 0.03 Mn 0.01 (OH)2, the preparation process is as follows:
[0174] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=96:3:1; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0175] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.50, the ammonia concentration is maintained at 5.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min. After the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0176] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.00, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out. By fine-tuning the feed rate of solution B and solution C, the reaction solution was heated to 50° C. and stirred at a constant temperature. The pH value of the reaction system is controlled to be 10.05-10.15 and the ammonia concentration is 4.6-5.4 g / L by adjusting the feed rate of liquid C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seed crystals are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 grows stably to 20.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.96 Co 0.03 Mn 0.01 (OH)2 cathode material precursor.
[0177] (2) Preparation of positive electrode materials
[0178] The positive electrode material precursor prepared in this embodiment was mixed evenly with lithium hydroxide in a ratio of 1:1.08, and then sintered at 530° C. for 10 h to obtain a positive electrode material.
[0179] Example 7
[0180] (1) Preparation of cathode material precursor:
[0181] The positive electrode material precursor prepared in this embodiment has the chemical formula Ni 0.40 Co 0.10 Mn 0.50 (OH)2, the preparation process is as follows:
[0182] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=40:10:50; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0183] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.50, the ammonia concentration is maintained at 5.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min. After the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0184] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.00, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out. By fine-tuning the feed rate of solution B and solution C, the reaction solution was heated to 50° C. and stirred at a constant temperature. The pH value of the reaction system is controlled to be 10.05-10.15 and the ammonia concentration is 4.6-5.4 g / L by adjusting the feed rate of liquid C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seed crystals are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 of the particles grows stably to 10.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.40 Co 0.10 Mn 0.50 (OH)2 cathode material precursor.
[0185] (2) Preparation of positive electrode materials
[0186] The positive electrode material precursor prepared in this embodiment was mixed evenly with lithium hydroxide in a ratio of 1:1.08, and then sintered at 700° C. for 10 hours to obtain a positive electrode material.
[0187] Comparative Example 1
[0188] (1) Preparation of cathode material precursor:
[0189] The positive electrode material precursor chemical formula prepared in this comparative example is Ni 0.96 Co 0.03 Mn 0.01 (OH)2, the preparation process is as follows:
[0190] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=96:3:1; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0191] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.50, the ammonia concentration is maintained at 5.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min. After the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0192] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.50, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out. By fine-tuning the solution B and solution C, the reaction mixture was stirred at a constant temperature. The pH value of the reaction system is controlled to be 10.40-10.50 and the ammonia concentration is 7.0-8.0 g / L by adjusting the feed rate of liquid C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seed crystals are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 of the particles grows stably to 10.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.96Co 0.03 Mn 0.01 (OH)2 cathode material precursor.
[0193] (2) Preparation of positive electrode materials
[0194] The positive electrode material precursor prepared in this comparative example was uniformly mixed with lithium hydroxide in a ratio of 1:1.08, and then sintered at 750° C. for 10 hours to obtain a positive electrode material.
[0195] Comparative Example 2
[0196] (1) Preparation of cathode material precursor:
[0197] The positive electrode material precursor chemical formula prepared in this comparative example is Ni 0.70 Co 0.10 Mn 0.20 (OH)2, the preparation process is as follows:
[0198] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=70:10:20; a sodium hydroxide solution with a solute mass fraction of 19.9 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 15.7 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.55, the mass concentration of ammonia solution was controlled to be 5.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 47°C.
[0199] Solution A, solution B and solution C are simultaneously introduced into the bottom liquid in the reaction container, and a first coprecipitation reaction is carried out under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 8.0% / h, 6.0% / h and 0.18% / h of the volume of the reaction container, respectively. During the reaction, the pH of the reaction system is controlled to be stable within the range of 9.90-10.00. At the beginning of the reaction, the stirring device is controlled to stir at a speed of 200.35 r / min. During the reaction, the stirring is reduced by 20-25 r / min every 10 hours, and the final stirring is maintained at 136.3 rpm / min until the particle size D50 of the particles grows stably to 4.0±0.3 μm, thereby obtaining a hydroxide slurry, and the hydroxide slurry is solid-liquid separated to obtain a precipitate. After washing, drying and sieving the precipitate, a chemical formula of Ni is obtained. 0.70 Co 0.10 Mn 0.20 (OH)2 cathode material precursor.
[0200] (2) Preparation of positive electrode materials
[0201] The positive electrode material precursor prepared in this comparative example was uniformly mixed with lithium hydroxide in a ratio of 1:1.08, and then sintered at 550° C. for 10 h to obtain a positive electrode material.
[0202] Comparative Example 3
[0203] (1) Preparation of cathode material precursor:
[0204] The positive electrode material precursor chemical formula prepared in this comparative example is Ni 0.96 Co 0.03 Mn 0.01 (OH)2, the preparation process is as follows:
[0205] A metal salt solution with a total metal ion mass concentration of 112 g / L was prepared as solution A, wherein the metal salts used in solution A were nickel sulfate, cobalt sulfate and manganese sulfate, and the molar ratio of nickel, cobalt and manganese was Ni:Co:Mn=96:3:1; a sodium hydroxide solution with a solute mass fraction of 30.5 wt% was prepared as solution B; an ammonia solution with a solute mass fraction of 22.5 wt% was prepared as solution C; pure water, solution B and solution C were added into a reaction container to prepare a base solution, the pH value of the base solution was controlled to be 11.95, the mass concentration of ammonia solution was controlled to be 10.0 g / L, nitrogen was introduced as a protective gas, and the base solution was heated to 50°C.
[0206] Simultaneously introducing solution A, solution B and solution C into the bottom liquid in the reaction container, and performing a first coprecipitation reaction under a protective gas atmosphere, wherein the feeding rates of solution A, solution B and solution C are 10.0% / h, 3.6% / h and 0.25% / h of the volume of the reaction container, respectively, and during the reaction, the pH of the reaction system is controlled to be maintained at 11.00, the ammonia concentration is maintained at 10.0 g / L, and the stirring device is controlled to stir at a speed of 185.50 r / min, and after the reaction is stable, solid-liquid separation is performed to obtain nickel-cobalt-manganese hydroxide seed crystals with a particle size D50 of 3.0 μm;
[0207] Pure water, solution B, solution C and nickel-cobalt-manganese hydroxide seed crystals were added to another reaction container to prepare a reaction solution, the pH value of the reaction solution was controlled to be 10.00, the mass concentration of ammonia water in the reaction solution was 5.0 g / L, nitrogen was introduced as a protective gas, and the reaction solution was heated to 50° C. and stirred at a constant temperature. Solution A, solution B and solution C were simultaneously introduced into the reaction solution in the reaction container at the feed rate of the first coprecipitation reaction to carry out a second coprecipitation reaction. During the reaction, the feed and discharge were continuously carried out. By fine-tuning the feed rate of solution B and solution C, the reaction solution was heated to 50° C. and stirred at a constant temperature. The pH value of the reaction system is controlled to be 10.40-10.50 and the ammonia concentration is 4.6-5.4 g / L by adjusting the feed rate of liquid C. The stirring device is controlled to stir at a speed of 100.50 r / min. Nickel cobalt manganese hydroxide seed crystals are continuously added during the reaction to maintain the stability of the particle size until the particle size D50 of the particles grows stably to 10.0±0.3 μm to obtain a hydroxide slurry. The hydroxide slurry is solid-liquid separated to obtain a precipitate. The precipitate is washed, dried, and sieved to obtain a precipitate with a chemical formula of Ni 0.96 Co 0.03 Mn 0.01 (OH)2 cathode material precursor.
[0208] (2) Preparation of positive electrode materials
[0209] The positive electrode material precursor prepared in this comparative example was evenly mixed with lithium hydroxide in a ratio of 1:1.08, and then sintered at 620° C. for 10 h to obtain a positive electrode material.
[0210] Physical and chemical analysis
[0211] The positive electrode material precursors prepared in each embodiment and comparative example were characterized and tested, and the physical and chemical data obtained from the test were as follows: Figures 1 to 12 As shown in Table 1 and Table 2 below.
[0212] Table 1. Statistical table of physical and chemical data of cathode material precursors
[0213]
[0214] Table 2. Statistical table of physical and chemical data of cathode material precursors
[0215]
[0216] It should be noted that Figure 3 This is a cross-sectional view of the positive electrode material precursor CP prepared in Example 1 of the present application, Figure 3 R1 in the figure represents the outer shell of the secondary particle, and R2 represents the inner core of the secondary particle. The diameter of the inner core layer R2 accounts for 60% of the total diameter of the secondary particle, and the remaining 40% is the outer shell. Figure 3It can be clearly seen that the positive electrode material precursor secondary particles provided in the embodiment of the present application include a core layer R2 and an outer shell layer R1 along the radial direction, and the pore arrangement of the secondary particles increases from the inside to the outside. The pore diameter of the core layer R2 of the secondary particles is smaller than the pore diameter of the outer shell layer R1, and the cross-sectional porosity of the core layer R2 is smaller than the cross-sectional porosity of the outer shell layer R1. In contrast, the cross-sectional view of the positive electrode material precursor CP prepared in Comparative Example 1 ( Fig.12 ), the secondary particles are dense as a whole, and the pore arrangement is relatively uniform, and there is no obvious change in the pore arrangement along the radius direction of the secondary particles.
[0217] Electrochemical performance:
[0218] In order to verify the performance advantages of the positive electrode material precursors prepared in each embodiment and comparative example, button-type half-cells were assembled using the positive electrode materials prepared in each embodiment and comparative example for electrochemical performance testing. The preparation process of the button-type half-cells is as follows:
[0219] The positive electrode materials prepared in each embodiment and comparative example were respectively mixed with conductive carbon black and binder PVDF (polyvinylidene fluoride) in a ratio of 8:1:1 to form a slurry, which was coated on aluminum foil to make a positive electrode sheet. The negative electrode sheet used a metal lithium sheet, and the electrolyte used 1 mol / L LiPF6 / EC:DMC (volume ratio 1:1). In a vacuum glove box, the battery case, positive electrode sheet, negative electrode sheet, diaphragm, spring sheet, and gasket were assembled into a button-type half-cell.
[0220] The electrochemical performance test was carried out using a blue electric test system. The button half-cells made of the positive electrode materials of each embodiment and the comparative example were subjected to a 0.33C charge and discharge test and a 1C (1C = 210 mA / g) cycle test for 50 weeks under 3.0-4.3V conditions. The test results are shown in Table 3 below.
[0221] Table 3. Statistics of electrochemical performance test data
[0222]
[0223] It should be understood that the first coulombic efficiency in Table 3 above = first discharge capacity / first charge capacity × 100%. The first charge capacity can be calculated by the first coulombic efficiency and the first discharge capacity, so the specific data of the first charge capacity is omitted in Table 3.
[0224] Please refer to Tables 1 to 3 and Figure 1-Figure 9As shown, the particle size D50 of the secondary particles of the positive electrode material precursor prepared in Examples 1 to 7 is in the range of 6 to 25 μm, the average cross-sectional porosity is in the range of 25 to 55%, and the cross-sectional porosity of the inner core layer and the cross-sectional porosity of the outer shell layer are less than 1, that is, the cross-sectional porosity of the inner core layer is less than the cross-sectional porosity of the outer shell layer. The positive electrode material precursors provided in each embodiment can provide more porous structures, which are beneficial to promote the sintering mass transfer process during the preparation of the positive electrode material, reduce the sintering temperature during the preparation of the positive electrode material, and maintain the consistency of its crystal structure, so that after the battery is made, the positive electrode material The material has a more stable structure and more porous structure, which is also beneficial to improving the rate performance of the battery, so that the battery not only has a 0.33C first discharge capacity of more than 215.32mAh / g, but also has a 1C / 0.33C rate performance of more than 94.03% and a capacity retention rate of more than 90.23% after 50 cycles at 1C; in summary, the positive electrode material prepared based on the positive electrode material precursor provided in the embodiment of the present application can achieve an effective balance among the first discharge capacity, first coulomb efficiency, rate performance and cycle capacity retention rate of the battery compared with the comparative examples.
[0225] Specifically, compared with Comparative Example 1, the positive electrode material precursor prepared in Example 1 has the same composition as that in Comparative Example 1, and the particle size D50 is close. The secondary particles of the positive electrode material precursor in Example 1 include an inner core layer R2 and an outer shell layer R1 along the radial direction (reference Figure 3 ), the ratio of the cross-sectional porosity of the inner core layer to the cross-sectional porosity of the outer shell layer is 0.22, and the ratio of the pore diameter is 0.65, indicating that the cross-sectional porosity and pore diameter of the inner core layer are smaller than those of the outer shell layer, and the overall average cross-sectional porosity of the secondary particles is 43.4%. The secondary particles have a larger average cross-sectional porosity, and the sintering temperature required for the positive electrode material is lower. The battery made of the positive electrode material has been tested to show an initial discharge capacity of 238.09 mAh / g at 0.33C, an initial coulombic efficiency of 94.54%, a 1C / 0.33C rate performance of 95.16%, and a capacity retention rate of 92.41% after 50 cycles at 1C; on the other hand, in Comparative Example 1, the capacity retention rate of the positive electrode material is 238.09 mAh / g at 0.33C, an initial coulombic efficiency of 94.54%, a 1C / 0.33C rate performance of 95.16%, and a capacity retention rate of 92.41% after 50 cycles at 1C. Fig.12It can be seen that the internal and external stratification of the positive electrode material precursor of Comparative Example 1 is not obvious, and the average cross-sectional porosity of the secondary particles is 21.5%, the average cross-sectional porosity is low, and the sintering temperature required for the positive electrode material is high (the sintering temperature required for the positive electrode material is 750°C, which is much higher than that of Example 1). The 0.33C first discharge capacity of the battery is 228.91mAh / g, the 0.33C first coulomb efficiency is 88.14%, the 1C / 0.33C rate performance is 87.52, and the capacity retention rate after 1C cycle 50 times is 88.12%. All electrochemical performance indicators are lower than those of Example 1, indicating that the secondary particles of the positive electrode material precursor are in the range of particle size D50 of 6 to 25μm, the average cross-sectional porosity is in the range of 25 to 55%, and the cross-sectional porosity of the inner core layer of the secondary particles is less than the cross-sectional porosity of the outer shell layer, which is more conducive to reducing the sintering temperature required for the positive electrode material, and is more conducive to the effective balance of the first discharge capacity, the first coulomb efficiency, the rate performance and the cycle capacity retention rate.
[0226] Compared with Example 3, Comparative Example 2 has the same cathode material precursor composition as Example 3, but the secondary particle size D50 of the cathode material precursor of Comparative Example 2 is 4 μm, which is much smaller than the secondary particle size D50 of the cathode material precursor of Example 3, and the other morphological parameters are relatively close. The first discharge capacity, first coulomb efficiency, rate performance and cycle capacity retention rate of the cathode material of Comparative Example 2 are all lower than those of Example 3, especially the first discharge capacity is significantly reduced, indicating that too small secondary particle size D50 is not conducive to the improvement of capacity performance, further verifying that the secondary particles of the cathode material precursor are in the range of particle size D50 of 6 to 25 μm and the average cross-sectional porosity is in the range of 25 to 55%, and the cross-sectional porosity of the inner core layer of the secondary particles is smaller than the cross-sectional porosity of the outer shell layer, which is more conducive to the effective consideration of the first discharge capacity, first coulomb efficiency, rate performance and cycle capacity retention rate of the battery.
[0227] Compared with Example 1, Comparative Example 3 has the same positive electrode material precursor composition as Example 1, but the core layer / shell layer cross-sectional porosity ratio of the secondary particles of the positive electrode material precursor of Comparative Example 3 is greater than 1, the secondary particles are loose inside and tight outside, and the other morphological parameters are relatively close. The first discharge capacity, first coulomb efficiency, rate performance and cycle capacity retention rate of the positive electrode material of Comparative Example 3 are all lower than those of Example 1, indicating that when the secondary particle size D50 is in the range of 6 to 25 μm, the average cross-sectional porosity is in the range of 25 to 55%, and the core layer cross-sectional porosity of the secondary particles is smaller than the shell layer cross-sectional porosity, it is more conducive to effectively taking into account the first discharge capacity, first coulomb efficiency, rate performance and cycle capacity retention rate of the battery.
[0228] Compared with Example 1, the specific surface area BET of the secondary particles of the positive electrode material precursor in Example 2 is smaller than that in Example 1, and the specific surface area BET is not within the range of 55 to 87 m 2 / g range, the other morphological parameters are relatively close to those of Example 1. The first discharge capacity, first coulombic efficiency and rate performance of the positive electrode material of Example 2 are slightly lower than those of Example 1, indicating that the larger specific surface area of the positive electrode material precursor is more conducive to improving the battery capacity performance and rate performance.
[0229] Compared with Example 1, Example 4 has the same positive electrode material precursor composition. Although the ratio of the cross-sectional porosity of the core layer of the secondary particles of the positive electrode material precursor to the cross-sectional porosity of the shell layer, the ratio of the pore diameter of the core layer of the secondary particles to the pore diameter of the shell layer, and the average cross-sectional porosity of the secondary particles in Example 4 are significantly higher than those in Example 1, the ratio of the cross-sectional porosity of the core layer of the secondary particles to the cross-sectional porosity of the shell layer is 0.78, which exceeds the range of 0.15 to 0.50, and the ratio of the pore diameter of the core layer of the secondary particles to the pore diameter of the shell layer is 0.9. 0, exceeding the range of 0.30-0.80, the pore structure of the inner core layer of the secondary particles is relatively loose compared with that of the inner core layer of the positive electrode material precursor secondary particles in Example 1, and the capacity retention rate of the positive electrode material in Example 4 after 1C cycle 50 times is 90.23%, which is significantly lower than that in Example 1, indicating that the cross-sectional porosity of the inner core layer of the secondary particles and the cross-sectional porosity of the outer shell layer are in the range of 0.15-0.50, and the ratio of the pore diameter of the inner core layer of the secondary particles to the pore diameter of the outer shell layer is in the range of 0.30-0.80, which is more conducive to the improvement of the battery cycle retention rate.
[0230] Compared with Example 1, Example 5 uses 1 mol% Al element to dope the positive electrode material precursor. The capacity retention rate of the battery made of the positive electrode material of Example 5 after 50 1C cycles is significantly improved compared with that of Example 1, indicating that the positive electrode material precursor can further improve the cycle performance of the battery through specific doping elements.
[0231] Compared with Example 1, the particle size D50 of the secondary particles of the positive electrode material precursor in Example 6 is 20.5 μm, which is significantly larger than that in Example 1, and the average cross-sectional porosity is 53.5%, which is slightly higher than that in Example 1. The other morphological indicators are close to those in Example 1. The first discharge capacity and rate performance of the battery made from the positive electrode material of Example 6 are improved compared with those of Example 1, indicating that a larger particle size D50 and a larger average cross-sectional porosity are more conducive to improving the battery capacity performance and rate performance.
[0232] In Example 7 compared with Example 1, the Ni molar content of the positive electrode material precursor accounts for 40% of the total metal element content, which is much lower than that of Example 1, and is a low-nickel and high-specific surface area product. The battery made of the positive electrode material has a significantly low first discharge capacity, indicating that the nickel molar content in the positive electrode material precursor accounts for ≥50% of the total metal molar content, especially when it is greater than 75%, which is more conducive to improving the battery capacity performance.
[0233] In summary, the cathode material precursor provided in the embodiment of the present application has an optimized design of morphology and structure, and the particle size D50 of the secondary particles of the cathode material precursor is 6 to 25 μm, the surface of the secondary particles is porous, and the average cross-sectional porosity is 25 to 55%, and the cross-sectional porosity of the inner core layer of the secondary particles is smaller than the cross-sectional porosity of the outer shell layer, which is beneficial to improving the battery capacity, rate performance and cycle performance, thereby achieving an effective balance among the battery capacity performance, cycle performance and rate performance.
[0234] The various technical features described above can be combined arbitrarily. Although all possible combinations of these technical features are not described, any combination of these technical features should be considered to be covered by this specification as long as there is no contradiction in such combination.
[0235] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A cathode material precursor, wherein the cathode material precursor is a transition metal hydroxide, characterized in that: The positive electrode material precursor includes secondary particles composed of primary particles, and the particle size D50 of the secondary particles is 6 to 25 μm; The secondary particles have a porous surface structure and an average cross-sectional porosity of 25 to 55%; The secondary particle comprises an inner core layer and an outer shell layer along the radial direction, and the cross-sectional porosity of the inner core layer of the secondary particle is smaller than the cross-sectional porosity of the outer shell layer.
2. The cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor is a nickel-containing hydroxide, and the percentage of nickel molar content in the positive electrode material precursor to the total metal molar content is ≥50%; preferably ≥75%; And / or, the specific surface area of the secondary particles is 45 to 100 m 2 / g.
3. The cathode material precursor according to claim 1, characterized in that: The positive electrode material precursor satisfies at least one of the following conditions: (1) The surface of the outer shell layer of the secondary particles presents a honeycomb-like pore structure; (2) the pore diameter of the inner core layer of the secondary particles is smaller than the pore diameter of the outer shell layer; (3) The average pore diameter of the secondary particles is 200 to 600 nm; (4) The ratio of the pore diameter of the inner core layer to the pore diameter of the outer shell layer of the secondary particles is 0.30 to 0.80; (5) The ratio of the cross-sectional porosity of the inner core layer of the secondary particles to the cross-sectional porosity of the outer shell layer is 0.15 to 0.
50.
4. The cathode material precursor according to any one of claims 1 to 3, characterized in that: The positive electrode material precursor satisfies at least one of the following conditions: A. The particle size D50 of the secondary particles is 8 to 20 μm; B. The particle size distribution Span value of the secondary particles is 0.18 to 1.5, preferably 0.2 to 0.4; C. The specific surface area of the secondary particles is 50 to 100 m 2 / g, preferably 55-87m 2 / g; D. The surface density of the secondary particles is 35-85%; E. The average pore diameter of the secondary particles is 400 to 600 nm; F. The sphericity of the secondary particles is 80-100%; G. The percentage of nickel molar content in the positive electrode material precursor to the total metal molar content is ≥ 75%; H. The primary particles are in the form of flakes; I. The thickness of the primary particles is 3 to 33 nm.
5. The cathode material precursor according to any one of claims 1 to 3, characterized in that: The chemical formula of the positive electrode material precursor is Ni a Co b Mn c Me (1-a-b-c) (OH)2, wherein 0.50≤a≤1.00, 0≤b≤0.50, 0≤c≤0.50, 0.90≤a+b+c≤1.00, Me is a doping element; Optionally, the doping element Me includes at least one of B, P, Ti, Y, Zr, Ca, Nb, Mg, Al, W or La.
6. A method for preparing a cathode material precursor according to any one of claims 1 to 5, characterized in that: include: Preparing a metal salt solution, a precipitant solution and a complexing agent solution, and mixing a solvent, the precipitant solution and the complexing agent solution to obtain a base solution; The metal salt solution, the precipitant solution and the complexing agent solution are simultaneously introduced into the base liquid to carry out a synthesis reaction to obtain a hydroxide slurry; The hydroxide slurry is post-processed to obtain a positive electrode material precursor.
7. The method for preparing a cathode material precursor according to claim 6, characterized in that: The preparation method selects one or more of the following conditions: a. The synthesis reaction comprises: simultaneously introducing the metal salt solution, the precipitant solution and the complexing agent solution into the base liquid for a first coprecipitation reaction to obtain the hydroxide slurry; or simultaneously introducing the metal salt solution, the precipitant solution and the complexing agent solution into the base liquid for a first coprecipitation reaction, after obtaining target particle size seed crystals by reaction, the seed crystals are mixed with the metal salt solution, the precipitant solution and the complexing agent solution to obtain a reaction liquid, and the metal salt solution, the precipitant solution and the complexing agent solution are introduced into the reaction liquid for a second coprecipitation reaction to obtain the hydroxide slurry; b. The post-treatment comprises: sequentially performing solid-liquid separation, washing, drying and sieving on the hydroxide slurry to obtain a positive electrode material precursor; c. The raw materials of the metal salt solution include: nickel salt, cobalt salt, manganese salt and a combination of doped metal salts containing at least nickel salt; d. The precipitant comprises at least one of sodium hydroxide, potassium hydroxide, sodium carbonate or potassium carbonate; e. The complexing agent includes at least one of ammonia water, ammonium bicarbonate, ammonium carbonate, citric acid, sodium citrate, ammonium citrate, oxalic acid or ammonium oxalate; f. The total mass concentration of metal ions in the metal salt solution is 60 to 150 g / L; g. The solute mass fraction of the precipitant solution is 5.0 to 50.0 wt %; h. The solute mass fraction of the complexing agent solution is 0.5 to 50.5 wt %; i. The pH of the base solution is 10.00-12.00; j. The concentration of the complexing agent in the base solution is 4.0 to 15.0 g / L; k. The temperature of the base liquid is 45-80°C; 1. During the synthesis reaction, the feed rate of the metal salt solution is 1.00-10.00% / h of the volume of the reaction vessel; m. During the synthesis reaction, the feed rate of the precipitant solution is 0.30-10.30% / h of the volume of the reaction vessel; n. During the synthesis reaction, the feeding rate of the complexing agent solution is 0.01 to 0.90% / h of the volume of the reaction container; o. During the synthesis reaction, the concentration of the complexing agent in the reaction system is 0.5 to 20.0 g / L; p. During the synthesis reaction, the pH value of the reaction system is 9.50 to 11.50; q. The synthesis reaction is carried out under stirring conditions with a stirring speed of 50 to 1500 r / min; r. The reaction temperature of the synthesis reaction is 45-80°C.
8. A positive electrode material, characterized in that The raw material of the positive electrode material includes the positive electrode material precursor according to any one of claims 1 to 5 or the positive electrode material precursor prepared by the preparation method according to any one of claims 6 to 7.
9. A battery, characterized in that: The battery comprises an electrode made of the positive electrode material as claimed in claim 8.
10. An electrical equipment, characterized in that: Comprising the battery as claimed in claim 9.
Citation Information
Cited By
Positive electrode material and preparation method thereof, positive plate, battery and electric equipment
CN120127140A
Positive electrode material precursor, preparation method thereof, positive electrode material and lithium ion battery
CN120622566A
Positive electrode material precursor and preparation method and application thereof
CN121292540A
Method for preparing cobalt-manganese composite precursor through coprecipitation
CN121651448A